AB1026 Achieving Minimal Disease Activity and Remission in Psoriatic Arthritis Patients Treated Continuously with TNF Inhibitors for 2 Years in The Real Life. (15th July 2016) - Chimenti, M.S.; Triggianese, P.; Tonelli, M.; Conigliaro, P.; Gigliucci, G.; Novelli, L.; Sunzini, F.; Perricone, R.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory arthropathy commonly associated with psoriasis. Minimal disease activity (MDA) and remission represent treatment targets. However, their assessment is to date an unmet need in PsA patients. Objectives: Aim of the study was to prospectively evaluate MDA and remission in PsA patients who were treated with subcutaneous TNF inhibitors (iTNF), every 3/6 months for 2 years. Methods: Clinical and laboratory data from 221 PsA patients were analyzed (F:M=1.3, age 55±13 years, disease duration 12.3±6.1 years) at baseline (T0), after 22 (T22), 54 (T54) and 104 (T104) weeks from the beginning of TNFi (adalimumab n=94; etanercept n=84; golimumab n=43). Values of DAS28-CRP, CPDAI, and DAPSA were calculated, and MDA/remission were assessed at the all the time points. MDA was defined as the occurrence of 5/7 criteria, while remission was assessed as DAS28-CRP<2.6, DAPSA≤3.3, and CPDAI<2. Occurrences of comorbidities such as cardio-vascular, renal, respiratory, infectious, metabolic, neuropsychiatric and thyroid diseases were registered. Concomitant therapies (steroids and csDMARDs) and predictive factors of remission were analyzed in accordance with the above-mentioned scores. The Chi-square test was used to compare the remission rate at the follow-up and to analyze the predictive factors. Cohen's kappa analysis was performed to measure the concordance between clinimetric scores: kappa ≥0.6 was considered as a good agreement and kappa ≥0.8 was considered as an excellent agreement. Results: Prevalence of patients on DAS28 and DAPSA remission was significantly higher at T104 comparing to T0, T22 and T54 while patients on MDA and CPDAI remission were more frequent at T104 compared with T0 and T22 (Figure1 A). At all the time points, a good concordance between MDA and DAS28<2.6 occurred (k=0.63) and an excellent concordance was obtained between MDA, CPDAI<2 and DAPSA≤3.3 (k=0.81). At T22, patients with thyreopathies achieved the CPDAI remission in a lower percentage compared to patients without thyreopathies (P=0.02, OR=3.3) (Figure 1 B). At T104, the female sex was associated with a lower prevalence of patients on DAS28 remission (P=0.005, OR=2.3) and MDA (P=0.01, OR=2.7) while a lower percentage of patients with metabolic comorbidities was on DAS28 remission with the respect to patients without them (P=0.02, OR=3.3) (Figure1 B). Patients on concomitant steroid therapy were fewer at T22/54/104 with the respect to T0 (P<0.0001 for all the comparisons) while the rate of patients on csDMARDs was lower at T104 compared with T0 (P<0.01). Conclusions: In clinical practice, MDA and remission were achieved in a high prevalence of PsA patients during TNFi treatment with a rate that increased from 22 to 104 weeks. Tapering of the concomitant treatment was thus allowed. Predictors as thyreopathies, female sex, and metabolic comorbidities were associated with a lower probability to achieve clinical remission. Disclosure of Interest: None declared